Pengaruh Pelatihan Shalat untuk Menurunkan Prokrastinasi Akademik pada Mahasiswa - Muhamad Fauzan Azima; Nita Trimulyaningsih; Uly Gusniarti (Universitas Islam Indonesia, 2016)
As the purpose of this study was to investigate the effect of shalat's training to lower on student academic procrastination. The hypothesis is no effect of a decrease in academic procrastination among students who attend training shalat with students who are not trained to shalat. This study uses pretest and posttest control group design, in which the research subjects are students from various departments at